Nanoreactors for green catalysis - De Martino, M. Teresa; Abdelmohsen, Loai K. E. A.; Rutjes, Floris P. J. T.; van Hest, Jan C. M. (Beilstein Journal of Organic Chemistry, 2018)
Sustainable and environmentally benign production are key drivers for developments in the chemical industrial sector, as protecting our planet has become a significant element that should be considered for every industrial breakthrough or technological advancement. As a result, the concept of green chemistry has been recently defined to guide chemists towards minimizing any harmful outcome of chemical processes in either industry or research. Towards greener reactions, scientists have developed various approaches in order to decrease environmental risks while attaining chemical sustainability and elegancy. Utilizing catalytic nanoreactors for greener reactions, for facilitating multistep synthetic pathways in one-pot procedures, is imperative with far-reaching implications in the field. This review is focused on the applications of some of the most used nanoreactors in catalysis, namely: (polymer) vesicles, micelles, dendrimers and nanogels. The ability and efficiency of catalytic nanoreactors to carry out organic reactions in water, to perform cascade reaction and their ability to be recycled will be discussed.
Keywords: catalysis; dendrimers; green chemistry; nanogels; nanoreactors; micelles; polymersomes